2010
DOI: 10.1016/j.jad.2010.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the developmental course of depression

Abstract: Background There is ample evidence for female preponderance of major depressive disorder (MDD) in adolescence and adulthood. This study examined gender differences in the developmental course (i.e., incidence, duration, number of depressive episodes, and recovery rates) of MDD in non-referred adolescents and young adults. Methods Data from the Oregon Adolescent Depression Project were used to examine gender differences in the developmental course of MDD. Gender differences in the onset, duration, number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
158
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(199 citation statements)
references
References 45 publications
(53 reference statements)
30
158
0
11
Order By: Relevance
“…Given that individuals with depression in the USA are more likely to be living in poverty (Kessler et al, 2003), the current sample might better represent the population of depressed individuals that need to be studied and provided effective treatments than a more general sample. Gender is also an important consideration-it is likely that young men and women follow different pathways to depression (Marcus et al, 2005;Essau et al, 2010). Gender differences in overall incidence are seen both in the USA (Kessler et al, 2003) and in diverse international studies (Andrade et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Given that individuals with depression in the USA are more likely to be living in poverty (Kessler et al, 2003), the current sample might better represent the population of depressed individuals that need to be studied and provided effective treatments than a more general sample. Gender is also an important consideration-it is likely that young men and women follow different pathways to depression (Marcus et al, 2005;Essau et al, 2010). Gender differences in overall incidence are seen both in the USA (Kessler et al, 2003) and in diverse international studies (Andrade et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies examining transactional covariation between cannabis use and depressive symptoms should include samples of female adolescents based on their higher rates of depressive symptoms during adolescence and beyond (Essau et al, 2010;Weissman et al, 1993) as well as research suggesting a strong relationship between affective problems and cannabis use in females (Marmorstein et al, 2010;Patton et al, 2002). Last, more frequent assessments of both cannabis use and depressive symptoms would have provided a more fine-grained picture of the development of each construct over time.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…It is commonly suggested that a female preponderance in depression and anxiety is universal and substantial. The prevalence of depression and anxiety for women is approximately twice that for men (2)(3)(4)(5)(6). Although there are advocates for the implications of hypothalamic-pituitary-adrenal axis hyperactivity in the sex differentiation in some expressions of both depression and anxiety (7), it is not clear what underlies the sex gap in these affective disorders.…”
mentioning
confidence: 99%